Cannabis as medicine: The pros and cons - Michael T Okafor; Uzoamaka A Okoli; Uwamleeka Opoke; Germaine A Okafor; Elvis N Shu; Chikere A Anusiem (International Journal of Medicine and Health Development, 2023)
The use of cannabis for medical purposes has been a subject for discussion for so many years. Cannabis as a source of medical treatment first came to light in the 19th century. However, origins of cultivation of marijuana as a medical plant can be traced back to thousands of years. Attempts to completely legalize the use of cannabis for medical purposes are strongly contested in many places due to some of its negative effects on users physically, psychologically, and socially. This review is aimed to discuss the mechanism of action and pharmacogenetics of cannabinoids to elucidate its uses as medicine as well as negative effects. Online searches on the following database: Google Scholar, PubMed, Biomed Central, and SciELO were done. An attempt was made to review articles with keywords such as cannabis, cannabinoid receptors, genes, and medical marijuana. This review has highlighted with evidence the importance of genomic profiling to prevent side effects associated with predisposing genes for the benefit of patients who are medical candidates for medicinal cannabis use. Medical profiling via cannabinoid gene expression studies of patients who are medical candidates of cannabis could prevent the negative effects associated with its use.